On the mechanism of action of clonidine: Effects on single central neurones - Anderson, Caroline (1974)
1 Noradrenaline and clonidine were applied by microiontophoresis to single neurones in the cerebral cortex and medullary reticular formation of anaesthetized rats. 2 Of a total of 247 neurones studied, 79% of medullary units and 60% of cortical units responded in the same manner to both noradrenaline and clonidine. The usual response was a depression of neuronal firing rate. 3 It proved possible to antagonize some responses to both substances by the microiontophoresis of bulbocapnine, whilst leaving unaffected similar responses to 5-hydroxytryptamine. 4 On 13% of the cells, clonidine produced an increase of firing rate. This effect could not be attributed to a post-synaptic antagonism of tonically released endogenous noradrenaline, but may indicate a presynaptic action of clonidine, reducing noradrenaline release. 5 These observations are thought to support the idea that clonidine may have an agonist action on noradrenaline receptors in the brain.